Motorcycle Selection Decision Support System Using the Electre III Method - Florentina Dwi Widyastuti (Jurnal Mandiri IT, 2021)
n making a decision on the selection of a motorcycle, someone will consider various criteria to get the best decision. To simplify the process, an application program for motorcycle selection decision making is made in this thesis. The application program was built by applying the Electre III method which is able to solve problems with many criteria. The criteria used are divided into 2 parts, namely technical factors such as dimensions, front brakes, rear brakes, engine type, front suspension, rear suspension and cylinder volume; and subjective factors such as availability of spare parts, available service areas, credit process, motorcycle body, motorcycle color, after-sales price, spare part price, purchase price, fuel consumption, speed and durability. The system will search for motorcycles from the database whose subjective and technical factors are the same as those entered by the user. Furthermore, the system will compare the value of the criteria between the selected motorcycle alternatives.